2021
DOI: 10.1080/13880209.2021.1970198
|View full text |Cite
|
Sign up to set email alerts
|

Modified BuShenYiQi formula alleviates experimental allergic asthma in mice by negative regulation of type 2 innate lymphoid cells and CD4 + type 9 helper T cells and the VIP–VPAC2 signalling pathway

Abstract: Context Modified BuShenYiQi formula (M-BYF) is derived from BuShenYiQi formula, used for the treatment of allergic asthma. The exact effect and mechanism of M-BYF on the improvement of asthma remain unclear. Objective We investigated the mechanism underlying the therapeutic effect of M-BYF on allergic asthma. Materials and methods The asthma model was established in female BALB/c mice that were sensitized and challenged with ovalbumin (OVA). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 69 publications
(80 reference statements)
0
14
0
Order By: Relevance
“…A role for VIP in the development of asthma has also been demonstrated in studies involving mice lacking the VIP gene that exhibited spontaneous asthma features, such as peribronchial airway inflammation and the production of pro-inflammatory cytokines and AHR, which was partially reduced by administration of exogenous VIP [95]. Therefore, the development of long-acting VIP analogs with strong bronchodilatory effects [76,82] or modulators of the VIP-VPAC2 signaling pathway may provide clinically useful agents for the treatment of asthma [92].…”
Section: Vasoactive Intestinal Polypeptide (Vip)mentioning
confidence: 89%
See 1 more Smart Citation
“…A role for VIP in the development of asthma has also been demonstrated in studies involving mice lacking the VIP gene that exhibited spontaneous asthma features, such as peribronchial airway inflammation and the production of pro-inflammatory cytokines and AHR, which was partially reduced by administration of exogenous VIP [95]. Therefore, the development of long-acting VIP analogs with strong bronchodilatory effects [76,82] or modulators of the VIP-VPAC2 signaling pathway may provide clinically useful agents for the treatment of asthma [92].…”
Section: Vasoactive Intestinal Polypeptide (Vip)mentioning
confidence: 89%
“…The VIP immune response is mediated by specific receptors, namely vasoactive intestinal peptide receptor type 1 (VPAC-1) and type 2 (VPAC-2) [87]. VIP is a well-known anti-inflammatory factor that regulates the production of both anti-and pro-inflammatory mediators and the endogenous oxidant/antioxidant balance; reduces IL-1β-induced neutrophil recruitment to the airways; inhibits the activation of macrophages, dendritic cells and microglia [88][89][90]; and promotes a type 2 immune response via the VPAC-2 receptor, which is highly expressed on activated T cells and ILC2s [77,91,92]. Transgenic mice with high constitutive VPAC2 expression in T cells showed immediate-type allergic reaction, in contrast to mice with knockout of the VPAC2 receptor [91][92][93].…”
Section: Vasoactive Intestinal Polypeptide (Vip)mentioning
confidence: 99%
“…DC., and Epimedium brevicornu Maxim. A recent study (Huang M. et al, 2021) has reported that the modified BSYQF can alleviate airways inflammation, AHR, mucus hypersecretion, and collagen deposition via a decrease in the expression of the VIP-VPAC2 signaling pathway in the mouse model. BSYQF has more than 16 chemical constituents including acteoside, catalpol, and icariin.…”
Section: Bu-shen-yi-qi Fangmentioning
confidence: 99%
“…MBYF consists of five herbs, as shown in Table 1 [ 29 31 ]. Furthermore, in vivo and in vitro experiments show that MBYF and its compounds can significantly adjust inflammation and immunology [ 29 , 30 , 32 – 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…MBYF consists of five herbs, as shown in Table 1 [ 29 31 ]. Furthermore, in vivo and in vitro experiments show that MBYF and its compounds can significantly adjust inflammation and immunology [ 29 , 30 , 32 – 35 ]. Icariin in Yinyanghuo has anti-inflammatory effects, upregulates the amount of GRα, and promotes its nuclear translocation in inflammatory cell models and the lung tissue of inflammation animal models [ 36 , 37 ].…”
Section: Introductionmentioning
confidence: 99%